Patch Test and Repeated Open Application Test (ROAT) in Allergic Contact Dermatitis - Anggraeni Noviandini; Cita Rosita Sigit Prakoeswa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2014)
Background: The clinical relevance of patch test reaction is often difficult to determine. Repeated Open Application Test (ROAT) have been developed to further evaluate the significance of patch test result. Purpose: Understanding methods, procedures, and reactivity of patch test and ROAT, so thatmay be used to help identify with a high risk of developing allergic contact dermatitis. Reviews: The validity of patch test is limited. Various attempts have been made at modifying the patch test, primarily in order to increase the sensitivity of the skin and thus enhance the reliability and validity of the results, such as ROAT. Several experimental studies have compare the result of patch testing with the outcome of ROATs and these have defined correlations between the threshold concentration at patch testing (MEC) and outcome of ROAT, and also shed light on some factors that may influence the outcome of ROATs. Results of patch testing with serial dilutions of colophony, cinnamic aldehyde, and isoeugenol have shown concordance with the outcome of ROATs. On the other hand, poor correlation between patch test reactivity and ROAT were demonstrated in another study on isoeugenol,hydoxycitronellal, formaldehyde dan chromium. Conclusion: Patch test and ROAT are two methods that may be used toidentify allergen exposure and MEC Allergic Contact Dermatitis reaction.Key words: patch test, repeated open application test (ROAT), allergic contact dermatitis (ACD).